2020
DOI: 10.1097/md.0000000000021008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dexmedetomidine with chloral hydrate as sedatives for pediatric patients

Abstract: Background: Dexmedetomidine (Dex) and chloral hydrate (CH) are the most frequently used sedative agents in pediatric patients. We aimed to systematically review the literature comparing the efficacy and safety of Dex and CH for sedation in pediatric patients. Methods: Seven electronic databases and 3 clinical trial registry platforms were searched for articles published prior to October 2019. Randomized controlled trials (RCTs) evaluating the efficacy and safety of Dex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Although brimonidine has hypnotic and analgesic effects because it indirectly inhibits the ascending activation system of the reticular structure through the locus coeruleus, it does not block the awakening mechanism while accompanying sleep [ 18 ]. We found that during the hypnotic process elicited by injected administration of brimonidine to rabbits, they would be awakened in a short time by changing their body position and pulling their limbs hard.…”
Section: Discussionmentioning
confidence: 99%
“…Although brimonidine has hypnotic and analgesic effects because it indirectly inhibits the ascending activation system of the reticular structure through the locus coeruleus, it does not block the awakening mechanism while accompanying sleep [ 18 ]. We found that during the hypnotic process elicited by injected administration of brimonidine to rabbits, they would be awakened in a short time by changing their body position and pulling their limbs hard.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it is of great interest that CH anesthesia produced a pattern of EEG activity remarkably similar to urethane, as CH is considered an acceptable anesthetic for recovery surgeries [ 57 , 58 ], and indeed is still in use as a clinical sedative primarily for pediatric patients [ 59 ]. This suggests that CH could provide researchers an avenue to perform controlled neurophysiological manipulations under a sleep-like state of CH anesthesia, and then assess behavioral outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although brimonidine has hypnotic and analgesic effects because it indirectly inhibits the ascending activation system of the reticular structure through the locus coeruleus, it does not block the awakening mechanism while accompanying sleep [23] . We found that during the hypnotic process elicited by injected administration of brimonidine to rabbits, they would be awakened in a short time by changing their body position and pulling their limbs hard.…”
Section: Discussionmentioning
confidence: 99%